Broadband and high gain dielectric‐rod end‐fire antenna fed by a tapered ridge waveguide for K/Ka bands applications. Issue 8 (27th April 2020) - Zhang, Yuwei; Lin, Shu; Zhu, Baoqi; Cui, Jingxuan; Mao, Yu; Jiao, Jianlin; Denisov, Alexander
Abstract : In this study, a broadband and high gain dielectric‐rod end‐fire antenna are proposed for applications on both the K and Ka bands. By employing the double‐ridged waveguide (DRW) feeding structure which is composed of a coaxial line to tapered DRW transition, a parabolic tapered DRW, and a parabolic‐tapered flared parallel waveguide section, the impedance bandwidth of this proposed antenna is broadened to 84.5%. The dielectric‐rod with the double circular truncated cone structure acted as the main radiator of the proposed antenna is adopted to achieve higher gains and lower side‐lobe levels as compared to the traditional circular cone dielectric‐rod, while the four‐wedges structure inserted in the waveguide is developed as the matching section of the dielectric‐rod to further improve the impedance matching. The measured results show that this antenna can be operated in 17.9–44.1 GHz, and the measured gain changes from 9.9 to 15.5 dBi. Moreover, the radiation patterns are demonstrated with observed end‐fire characteristic in the overall operating band.